ILMU JARH WA AL-TA‘DI - Muhamad Basyrul Muvid; Berlian Tahta Arsyillah; Muammar (LPPM IAIN Kediri, 2022)
The purpose of this article is to examine in detail about the science of jarh wa al-ta'dil as a tool to assess hadith narrators in terms of weaknesses (jahr) and also advantages (ta'dil). The research method used is literature study. The study resulted that first, the urgency of the Science of al-jarh wa al-ta'dil as a step to determine whether the narration of a narrator can be accepted or should be rejected altogether. Second, the history of the science of jahr wa al-ta'dil has grown since the time of the companions. Third, the method or method of the ulama in explaining the behavior of the narrators and the conditions of the critics (al-jarh wa ta'dil) in assessing the narrators. Fourth, the conception and editorial of Jarh wa al-Ta'dil (lafaz-lafaz and maratib alfaz al-jarh wa al-ta'dil, contradictions (khilafiyah) between al-Jarh and al-Ta'dil, how to know al-jarh wa al-ta'dil, the critic (al-jarih) who evaluates the narrators, and the books that discuss the science of al-jarh wa al-ta'dil) Tujuan artikel ini adalah untuk mengkaji secara detail tentang Ilmu jarh wa al-ta’dil sebagai alat untuk menilai perawi hadits dalam segi kelemahan (jahr) dan juga keunggulan (ta’dil). Metode penelitian yang digunakan ialah studi kepustakaan. Kajian yang dihasilkan bahwa pertama, urgensi Ilmu al-jarh wa al-ta‘dil sebagai langkah untuk menetapkan apakah periwayatan seorang rawi itu dapat diterima atau harus ditolak sama sekali. Kedua, sejarah ilmu jahr wa al-ta’dil ini tumbuh sejak dari zaman sahabat. Ketiga, cara atau metode ulama dalam menjelaskan perilaku para perawi dan syarat-syarat kritikus (al-jarh wa ta’dil) dalam menilai rawi. Keempat, konsepsi dan redaksi Jarh wa al-Ta’dil (lafaz-lafaz dan maratib alfaz al-jarh wa al-ta’dil, pertentangan (khilafiyah) antara al-Jarh dan al-Ta’dil, cara mengetahui al-jarh wa al-ta’dil, kritikus (al-jarih) yang menilai rawi, dan kitab-kitab yang membahas ilmu al-jarh wa al-ta’dil).